Spontaneous cervical emphysema: a challenge in establishing a plausible etiology - Andrew CGJ; Ahmad NA; Hamal MH (International Journal of Medical Research and Review, 2016)
Spontaneous cervical emphysema occurs in the absence of previous disorders or intiating factors and often poses a challenge in establishing an etiology at presentation. We report a 23 year old lady who presented with extensive subcutaneous emphysema in which a clear etiology was not evident during the initial presentation.